The Distortion of Public Perception towards the Quick Count Results in 2019 Elections - Zamhasari Zamhasari; Dhea Elsa Novita; Elhanna Rizky Juliani; Sriatin Sriatin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2020)
This article discusses public beliefs in results of quick count in 2019 elections. There was a problem of differences in public perception of the quick count results which caused various polemics in the community. The phenomenon occurs when people disagree to accuse fraud and conspiracy by one of the candidates with the pollsters and the media. The theory explained that there are still people who have not been able to distinguish between original news or facts and hoax. Through a media framing analysis approach, this study explains the impact of divisions among the people who perceive very different quick count results. Based on the facts or data, voter distortion in the election against the quick count results is caused by the lack of political education and civic culture for election participants in Indonesia.